2016
DOI: 10.1080/01634372.2016.1235067
|View full text |Cite
|
Sign up to set email alerts
|

‘Growing Old’ in Shelters and ‘On the Street’: Experiences of Older Homeless People

Abstract: Homelessness among older people in Canada is both a growing concern, and an emerging field of study. This article reports thematic results of qualitative interviews with 40 people aged 46 to 75, carried out as part of a mixed-methods study of older people who are homeless in Montreal, Quebec, Canada. Our participants included people with histories of homelessness (n = 14) and persons new to homelessness in later life (n = 26). Interviews focused on experiences at the intersections of aging and homelessness inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…Grenier, Sussman, et al. (2016) report that older homeless people often experience a sense of ‘placeless’ ageing – deprived of the necessary material conditions from which they can build a meaningful home. Studies highlighted improvements in depressive symptoms among those who found stable housing compared with those who remained homeless (Brown et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Grenier, Sussman, et al. (2016) report that older homeless people often experience a sense of ‘placeless’ ageing – deprived of the necessary material conditions from which they can build a meaningful home. Studies highlighted improvements in depressive symptoms among those who found stable housing compared with those who remained homeless (Brown et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Authors suggest that it is incumbent upon services to strike a balance between providing intensive support while maintaining sufficient respect for older homeless adults’ need for independence (Crane & Warnes, 2010; Ogden, 2014). This body of work argues that it is crucial that older homeless adults are positioned as adaptable, independent and resilient individuals, who are not simply passive recipients of care and welfare (Grenier, Sussman, et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations